Why the Light Front Time x (+) is the Best Time Variable - Sales, Jorge Henrique; Suzuki, Alfredo Takashi [UNESP]; Santos, Gislan S. (Springer, 2015)
Investigating the coordinate transformations from the usual Minkowski's space-time to the light-front coordinates, we obtain two possible forms to represent the time coordinate in the light-front, x (+) and/or x (-), which usually is said to be equivalent and symmetric. We observe that this equivalence and symmetry is only apparent, since in the ultra-relativistic limit v -> c the former x (+) is well defined while the latter x (-) becomes singular and not well-defined. From this setting and choice we analyze the concept of time in quantum mechanics tunneling effect using the light front tools.